Congestive heart failure and cognitive functioning amongst older adults - Almeida,Osvaldo P. (2001)
BACKGROUND: Congestive heart failure is associated with decline in quality of life and, possibly, cognitive functions such as memory and attention. AIMS: The present study was designed to investigate the presence of cognitive impairment amongst patients with congestive heart failure (CHF). We hypothesised that CHF patients would have lower scores than elderly controls on general measures of cognitive functioning. METHODS AND RESULTS: We examined a sample of 50 consecutive patients admitted to hospital with CHF functional class III/IV and a convenience sample of 30 older adults assessed at the outpatient service of geriatric medicine of a teaching hospital in São Paulo, Brazil. All subjects were interviewed with the Cambridge Examination for Mental Disorders of the Elderly (CAMDEX), as well as the neuropsychological battery of the CAMDEX (CAMCOG), Mini-Mental State Examination (MMSE), Trail Making A and B, Digit Span, Digit Symbol, and Letter Cancellation Test. All CHF patients had left ventricular ejection fraction (EF) below 45% and all controls above 65%. The cognitive performance of CHF patients was significantly worse than controls for all cognitive assessments. Twenty-seven of 50 CHF patients had a MMSE total score lower than 24, compared with only 10/30 controls (p=0.073). Similarly, 36/49 and 9/30 CHF subjects and controls respectively had CAMCOG scores below 80 (p<0.001). Cognitive scores were significantly associated with EF, which was the most robust predictor of cognitive impairment according to the CAMCOG in a logistic regression model. CONCLUSION: Our results indicate that CHF is associated with significant levels of cognitive impairment and show that mental performance is, at least partly, a consequence of EF. Physicians should be prepared to assess the mental state of patients, as poor cognitive functioning may interfere with treatment compliance and management plan.